The costs of successful beneficiaries in proceedings brought under section 50 of the Administration of Justice Act 1985—Perry v Neupert. Issue 10 (15th November 2019) - Grantham, Andrew
Abstract: In this article, Andrew Grantham reviews the recent decision of the Court in Perry v Neupert in which HHJ Eyre QC reviewed the entitlement of successful beneficiaries to recover their costs in proceedings to remove the executor named in the testator's will and the extent to which in such circumstances the executor is entitled to an indemnity out of the assets of the estate.